2017
DOI: 10.1002/ajim.22797
|View full text |Cite
|
Sign up to set email alerts
|

Violence against emergency medical services personnel: A systematic review of the literature

Abstract: EMS leaders and personnel should work together with researchers to design, implement, evaluate and publish intervention studies designed to mitigate risks of violence to EMS personnel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
115
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(119 citation statements)
references
References 45 publications
2
115
1
1
Order By: Relevance
“…Today, workplace violence is one of the major challenges in the pre‐hospital setting (Maguire, O'meara, O'neill, & Brightwell, ) and pre‐hospital staff, including nurses, experience many violent acts against them in their workplace (Gormley, Crowe, Bentley, & Levine, ; Maguire, ). Workplace violence is the act or threat of violence, ranging from verbal abuse to physical assaults, directed towards persons at work or on duty (Department of Health & Human Services, ).…”
Section: Introductionmentioning
confidence: 99%
“…Today, workplace violence is one of the major challenges in the pre‐hospital setting (Maguire, O'meara, O'neill, & Brightwell, ) and pre‐hospital staff, including nurses, experience many violent acts against them in their workplace (Gormley, Crowe, Bentley, & Levine, ; Maguire, ). Workplace violence is the act or threat of violence, ranging from verbal abuse to physical assaults, directed towards persons at work or on duty (Department of Health & Human Services, ).…”
Section: Introductionmentioning
confidence: 99%
“…Emergency medical service (EMS) providers are first responders for public health and safety. In providing first aid, and stabilizing patients in emergency situations, such as assaults and disasters, EMS providers are often vulnerable to violence from several sources, including their patients . A study in Canada found that 26% of paramedics were exposed to physical assault and 67% were exposed to verbal abuse over the prior 12 months .…”
Section: Introductionmentioning
confidence: 99%
“…reported that 1% of ED presentations involved violence, and the incidence is increasing. Occupational violence is a significant burden on resources and paramedic well‐being, as paramedics are often managing risky situations outside of a controlled environment.…”
Section: Introductionmentioning
confidence: 99%